(untitled) (International Journal of Engineering and Computer Science, 2015)
The main aim of this project is to monitor the faults in a motor by wireless communication. In our proposal a solution to both electrical and mechanical based faults in an industrial machine is obtained based on WSN. The industrial machine model and its various types of faults are analyzed using a ARM9 LPC2929 processor. Although tremendous progress made in the past years still lot of problems needs to be resolved and the existing system based on the WSNs are short distance communication and need human interaction. The proposed system has capability to resolve all the issues which happen in the existing methods and proposed method offers long distance communication, safe operation, maintenance of time and increased operation reliability.